Androstadienone's influence on the perception of facial and vocal attractiveness is not sex specific. (April 2016) - Ferdenzi, Camille; Delplanque, Sylvain; Atanassova, Reni; Sander, David
Highlights: We investigated men's and women's perception of male and female faces and voices. We tested the effect of the odorous compound androstadienone on this perception. Androstadienone enhanced perceived attractiveness of the stimuli. Androstadienone modulated the time taken to categorize stimuli as attractive or not. These effects were not sex specific, with regard to rater and/or stimulus sex. Abstract: The androgen steroid androstadienone, an odorous compound emitted from the human axillary region, has recurrently been considered as a candidate compound involved in human chemical communication and mate choice. Although perception of androstadienone has been shown to influence several affective (mood), attentional, physiological and neural parameters, studies investigating its impact on human attractiveness remain unpersuasive because of incomplete designs (e.g., only female participants) and contradictory results. The aim of this study was to investigate how androstadienone may influence others' attractiveness. Specifically, we used a complete design (male and female raters, male and female faces and voices) to determine whether androstadienone influences the perception of social stimuli in a sex-specific manner, which would favor pheromonal-like properties of the compound, or in a more general manner, which would suggest that the compound has broader influences on human psychological responses. After comparing the ratings of men and women who were exposed to androstadienone masked in clove oil with those of men and women who were exposed to clove oil alone, we found that androstadienone enhanced the perceived attractiveness of emotionally relevant stimuli (opposite-sex stimuli in men and in fertile women). Response times for categorizing the stimuli as attractive or not were also affected by androstadienone, with longer response times in men and in fertile women and shorter response times in non-fertile women, irrespective of the stimulus sex. The results favor the hypothesis of general effects over sex-specific effects of androstadienone, thus questioning the relevance of focusing on that particular compound in the study of human attractiveness through body odor and encouraging the search for other semiochemicals that might be significant for human mate choice.